2021
DOI: 10.1108/pijpsm-06-2021-0083
|View full text |Cite
|
Sign up to set email alerts
|

Cops and COVID: an examination of California officers' perceptions and experiences while policing during a pandemic

Abstract: PurposeUsing online survey data from a sample of 440 police officers in California throughout May 2020, the current study collected time-sensitive information on officers' perceptions and departmental experiences in the wake of the pandemic. It examined officers' perceptions of agency responsivity as well as their perceptions of morale, stress and risk following agency responses and changes in policy patterns, service delivery innovations and other administrative challenges.Design/methodology/approachCOVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…When COVID-19 hit the nation, it created a wave of change, resulting in a chain reaction that affected the entire criminal justice system. The results of the study parallel the literature, highlighting the challenges faced by law enforcement agencies during the pandemic, including increased level of stress, financial difficulties, and concerns about the spread of COVID-19 among officers and inmates (Stogner et al, 2020;Shjarback & Magny, 2022;Maskály et al, 2022;Lum et al, 2022;Wright et al, 2022). What we found in our study is that, as bitter medicine is taken by a sick individual for the sake of healing, arduous precautions were put in place for the sake of overall safety and wellness.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…When COVID-19 hit the nation, it created a wave of change, resulting in a chain reaction that affected the entire criminal justice system. The results of the study parallel the literature, highlighting the challenges faced by law enforcement agencies during the pandemic, including increased level of stress, financial difficulties, and concerns about the spread of COVID-19 among officers and inmates (Stogner et al, 2020;Shjarback & Magny, 2022;Maskály et al, 2022;Lum et al, 2022;Wright et al, 2022). What we found in our study is that, as bitter medicine is taken by a sick individual for the sake of healing, arduous precautions were put in place for the sake of overall safety and wellness.…”
Section: Discussionsupporting
confidence: 80%
“…One of the first studies to examine the perceptions of policing during COVID-19 from the officers' standpoint rather than an organizational perspective was conducted in California among 440 police officers in 2020 (Shjarback & Magny, 2022). The findings showed that there was a correlation between the number of changes made within departments following COVID-19 that decreased contact between police and the public and a decrease in negative outlook (e.g., stress, low morale, and feelings of danger or risk).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effects of the coronavirus on American policing The pandemic affected routine policing (Shjarback and Magny, 2022), including initiating new policies related to the demand for and supply of police services (Lum et al, 2023). Early assessments of police practices during the pandemic suggested that police departments lacked PPE, had different experiences with policing mandates, experienced reduced calls for service (Lum et al, 2023) in general and increased calls for specific types of incidents, such as domestic disputes (Ashby, 2020;Hansen and Lory, 2020;Nix and Richards, 2021;Richards et al, 2021), and altered or delayed police academy operations (Gaub et al, 2022;White et al, 2022).…”
Section: Review Of Literaturementioning
confidence: 99%
“…The pandemic affected routine policing (Shjarback and Magny, 2022), including initiating new policies related to the demand for and supply of police services (Lum et al. , 2023).…”
Section: Review Of Literaturementioning
confidence: 99%
“…This study expands the literature on police perceptions of pandemic responses to provide a more global perspective. Shjarback and Magny (2021) administered an online survey to members of the Peace Officers Research Association of California (n 5 440) to understand their perceptions and departmental experiences with management of the pandemic. Their findings show that when departments implemented more changes that reduced police contact with the public, officers had (1) more positive perceptions about their agency's responsivity to officer needs and (2) an increased positive outlook overall.…”
Section: Police Perceptions Of Pandemic Policingmentioning
confidence: 99%